The Principle Pacta Sunt Servanda: The Alliance of Sahel States and Treaty Termination with France - Ogbologu, Ogonna Beauty (PERSPEKTIF, 2025)
The concept of Pacta Sunt Servanda is crucial for maintaining the stability of the international legal system, as it requires agreements to be respected and upheld as legally binding. However, the changing socio-political dynamics between former colonial powers and post-colonial states create difficulties in directly implementing this principle. This study explores this principle focusing on Mali, Burkina Faso, and Niger (AES)'s ability to terminate the security and economic treaties with France unilaterally. Adopting a mixed method, which entails a triangulation between doctrinal and case study research approaches, this study investigates the sustainability of this international law principle in the face of Africa's awakening in the changing global power landscape. The aim is to uncover the patterns and motivations behind these states' disengagement decisions. The findings reveal that while Pacta Sunt Servanda supports respecting treaties, exceptions based on changes in circumstances may provide legal grounds for termination. The conclusion emphasizes that while the AES's unilateral terminations present economic and legal challenges, specific conditions could justify such actions within the framework of international law, hence the need for a careful and comprehensive interpretation of treaty obligations and rights.